RECOVERY TEMBAGA DARI LARUTAN TEMBAGA SULFAT MELALUI METODE SEMENTASI MENGGUNAKAN BESI - Kostiawan Sukamto (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2023)
This study aims to optimize the copper recovery process from copper sulfate solution using the cementation method with iron as the precipitating agent. This method offers an efficient and sustainable solution to address the challenges of copper recovery from copper sulfate solutions, which has become increasingly crucial due to the declining supply of high-grade copper ore. The variables optimized in this research encompass the optimization of stirring speed (50 RPM to 300 RPM), iron addition (0.5 to 3 times the stoichiometric reaction), temperature (30 to 70°C), and reaction time (15 to 120 minutes). The research results indicate that the optimal conditions for copper recovery are achieved at a stirring speed of 200 RPM, iron addition of 2 times the stoichiometric reaction, a temperature of 70°C, and a reaction time of 120 minutes. Under these conditions, the percentage of copper recovery from the copper sulfate solution using the cementation method reaches 99.37%, demonstrating a high level of efficiency in this approach.